Data from: The leaf economic and plant size spectra of European forest understory vegetation ... - Padullés Cubino, Josep; Biurrun, Idoia; Bonari, Gianmaria; Braslavskaya, Tatiana; Font, Xavier; Jandt, Ute; Jansen, Florian; Rašomavičius, Valerijus; Willner, Wolfgang; Chytrý, Milan (Dryad, 2021)
Forest understories play a vital role in ecosystem functioning and the provision of ecosystem services. However, the extent to which environmental conditions drive dominant ecological strategies in forest understories at the continental scale remains understudied. Here, we used ~29,500 forest vegetation plots sampled across Europe and classified into 25 forest types to explore the relative role of macroclimate, soil pH, and tree canopy cover in driving abundance-weighted patterns in the leaf economic spectrum (LES) and plant size spectrum (PSS) of forest understories (shrub and herb layers). We calculated LES using specific leaf area (SLA) and leaf dry matter content (LDMC), and PSS using plant height and seed mass of vascular plant species found in the understories. We found that forest understories had more conservative leaf economics in areas with more extreme mean annual temperatures (mainly Fennoscandia and the Mediterranean Basin), more extreme soil pH, and under more open canopies. Warm and summer-dry ... : All vegetation data used in this study were obtained from the European Vegetation Archive (EVA; http://euroveg.org; project number 82). Further details on data collection and associated databases can be found on the EVA website. Trait data used in the study were obtained from the TRY database (https://www.try-db.org/TryWeb/Home.php). See "Material and Methods" in the reference paper for details on the processing of these data. ...